2002
DOI: 10.1086/338122
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interferon‐γ in Murine Pneumococcal Pneumonia

Abstract: To determine the role of interferon (IFN)-gamma in pneumonia, IFN-gamma receptor-deficient (IFN-gamma R(-/-)) and 129/Sv (wild-type [wt]) mice were inoculated intranasally with Streptococcus pneumoniae. Although mortality did not differ between the groups 48 h after inoculation, IFN-gamma R(-/-) mice had significantly fewer pneumococci in their lungs than the wt mice. Similarly, IFN-gamma(-/-) mice had fewer colony-forming units in lungs than wt mice. The relatively increased resistance of IFN-gamma R(-/-) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
59
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 52 publications
6
59
0
Order By: Relevance
“…Possibly, the role of IL-12 is more prominent during Gramnegative (K. pneumoniae) pneumonia than in Gram-positive (S. pneumoniae) pneumonia. Recent data generated in our laboratory indicate that the role of endogenous IFN-␥ is opposite to the role of endogenous IL-18 in this pneumonia model (45). Indeed, both IFN-␥R-deficient and IFN-␥-deficient mice demonstrated a reduced outgrowth of pneumococci when compared with their respective WT strains in association with a diminished influx of neutrophils to BALF.…”
Section: Discussionmentioning
confidence: 86%
“…Possibly, the role of IL-12 is more prominent during Gramnegative (K. pneumoniae) pneumonia than in Gram-positive (S. pneumoniae) pneumonia. Recent data generated in our laboratory indicate that the role of endogenous IFN-␥ is opposite to the role of endogenous IL-18 in this pneumonia model (45). Indeed, both IFN-␥R-deficient and IFN-␥-deficient mice demonstrated a reduced outgrowth of pneumococci when compared with their respective WT strains in association with a diminished influx of neutrophils to BALF.…”
Section: Discussionmentioning
confidence: 86%
“…For example, the ELR-positive CXC chemokine LIX and the CC chemokine MCP-1 each facilitate neutrophil recruitment in the lungs (30,31). In addition, IL-17 and IFN-␥ are T cell-derived cytokines that can augment neutrophil recruitment to bacteria in the lungs (32)(33)(34)(35)(36). The concentrations of these four cytokines were measured in WT and TM mice with pneumococcal pneumonia (Table I).…”
Section: Chemokine Expressionmentioning
confidence: 99%
“…More recently, it was shown that S. pneumoniae may also be recognized by inflammasomes that are dependent upon the adaptor molecule ASC (16)(17)(18)(19). Together, these pathways initiate immune activation and lead to production of inflammatory cytokines and chemokines that subsequently mediate the recruitment of leukocytes to the site of infection (20)(21)(22)(23)(24)(25)(26). However, when this occurs within the brain, the ensuing inflammatory response is argued to ultimately cause neuronal damage and/ or death (9,10).…”
mentioning
confidence: 99%
“…In patients with S. pneumoniae sepsis, plasma IFN-g levels were reported to be elevated, and circulating levels of the cytokine correlated with mortality (44). In murine models, IFN-g inhibition/ ablation was reported to lead to decreased survival (25,26,45) or to have no effect on mortality (23,46). Furthermore, in the absence of IFN-g, decreased levels of chemokines involved in neutrophil recruitment, as well as neutrophils themselves, were reported by some groups (23,26), and this was associated with a lower bacterial load (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation